Unique Indications for Covered Stent Grafts in Neuroradiology Departments of Level 1 Trauma Centers - Goelz, Leonie; Kreißl, Lutz; Gutowski, Pawel; Sparenberg, Paul; Kirsch, Michael; Mutze, Sven (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective To describe unique indications for covered stent grafts in trauma-associated cerebrovascular injuries.Patients Between 2006 and 2018, five patients with cerebrovascular injuries were treated with a covered stent graft. We present a retrospective analysis of technique and outcomes.Results In all cases stent deployment was successful. Endoleaks occurred in two cases requiring additional transvenous embolization of a carotid cavernous fistula (CCF) in one patient. Two cases of in-stent thrombosis were observed during intervention and 2 days postintervention in a patient with a long-segment dissection of the internal carotid artery (ICA) and another patient with a contained ICA rupture, both of which could not be prepared with dual antiplatelet therapy. Intravenous heparin and intra-arterial tirofiban dissolved in-stent thrombosis efficiently. One CCF and an iatrogenic vertebral artery injury were covered adequately with GraftMaster stent grafts.Conclusion Patient selection with regard to individual anatomy and the site of vascular lesions is essential for an uncomplicated deployment of covered stent grafts and the success of therapy. Management of dual antiplatelet therapy, anticoagulation, and an escalation of medication in cases of in-stent thrombosis require expertise, a strict therapeutic regime, and an evaluation of individual risks in polytraumatized patients.
Keywords: GraftMaster; Jostent; cerebrovascular injury; trauma; covered stent graft